Trends in drug overdose deaths among adults 65 years of age and older in Canada (2000–2022) - Sameer Imtiaz; Farihah Ali; Nat Kaminski; Cayley Russell; Jürgen Rehm (Drug and Alcohol Dependence Reports, 2024)
Background: Although young adults and middle-aged adults have borne the brunt of the drug overdose crisis in Canada, older adults are also at an increased risk of harms. We examined trends in drug overdose deaths and opioid overdose deaths among adults 65 years of age and older. Methods: Age-standardized rates of drug overdose deaths in Canada (2000–2022) and of opioid overdose deaths in Ontario (2003–2021) were computed. Drug overdose deaths were based on vital statistics registries, while opioid overdose deaths were based on toxicologic testing. Trends were characterized using joinpoint regression. Results: Drug overdose deaths among adults 65 years of age and older in Canada rose from 4.3 to 9.9 deaths per million in the entire population between 2000 and 2022 (Average Annual Percentage Change [AAPC; 95 % CI]: 3.1 % [2.6 %-3.6 %]). Increases were observed in males (AAPC [95 % CI]: 4.0 % [3.1 %-4.9 %]), females (2.1 % [1.0 %-3.2 %]) and unintentional deaths (6.0 % [1.0 %-11.3 %]) after stratification by sex and manner of death. Opioid overdose deaths among adults 65 years of age and older in Ontario increased from 1.5 to 5.2 deaths per million in the entire population between 2003 and 2021 (AAPC [95 % CI]: 7.5 % [4.5 %-10.5 %]). Conclusions: Drug overdose deaths more than doubled in Canada and opioid overdose deaths more than tripled in Ontario among adults 65 years of age and older during the past two decades. These findings indicate a need for education of patients, prioritization of harm reduction interventions, screening, intervention and treatment and adherence to prescribing guidelines.